Proinflammatory Cytokine Modulates Intracellular Calcium Handling and Enhances Ventricular Arrhythmia Susceptibility - Tsai, Yung-Nan; Hsiao, Ya-Wen; Lin, Shien-Fong; Chan, Yi-Hsin; Hsieh, Yu-Cheng; Tang, Wei-Hua; Lee, An-Sheng; Huang, Yu-Ting; Li, Hsing-Yuan; Chao, Tze-Fan; Higa, Satoshi; Wu, Tsu-Juey; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: The mechanism of Interleukin-17 (IL-17) induced ventricular arrhythmia (VA) remains unclear. This study aimed to investigate the effect of intracellular calcium (Cai) handling and VA susceptibility by IL-17. Methods: The electrophysiological properties of isolated perfused rabbit hearts under IL-17 (20 ng/ml, N=6) and the IL-17 with neutralizer (0.4 μg/ml, N=6) were evaluated using an optical mapping system. The action potential duration (APD) and Cai transient duration (CaiTD) were examined, and semiquantitative reverse transcriptase-polymerase chain reaction analysis of ion channels was performed. Results: There were longer APD80, CaiTD80 and increased thresholds of APD and CaiTD alternans, the maximum slope of APD restitution and induction of VA threshold in IL-17 group compared with those in IL-17 neutralizer and baseline groups. During ventricular fibrillation, the number of phase singularities and dominant frequency were both significantly greater in IL-17 group than in baseline group. The mRNA expressions of the Na+/Ca2+ exchanger, phospholamban, and ryanodine receptor Ca2+ release channel were upregulated, and the subunit of L-type Ca2+ current and sarcoplasmic reticulum Ca2+-ATPase 2a were significantly reduced in IL-17 group compared to baseline and IL-17 neutralizer group. Conclusions: IL-17 enhanced CaiTD and APD alternans through disturbances in calcium handling, which may increase VA susceptibility.